Primary and additional treatment preference in aggressive retinopathy of prematurity and type 1 retinopathy of prematurity. Issue 1 (24th January 2023) - Jang, Ji Hye; Kang, Yong Koo; Park, Han Sang; Kim, Kiyoung; Kim, Sung Soo; Han, Jae Yong; Kim, Hyun Wong; Bang, Jong Wook; Song, Jae Shin; Park, Sang Jun; Woo, Se Joon; Joo, Kwang Sic; et al.
Abstract : Objective: This study aimed to evaluate the preference for antivascular endothelial growth factor (anti-VEGF) versus laser ablation therapy as primary and additional treatment in aggressive retinopathy of prematurity (ROP) and type 1 ROP. Methods: This multicentre retrospective study was conducted at nine medical centres across South Korea. A total of 94 preterm infants with ROP who underwent primary treatment between January 2020 and December 2021 were enrolled. All eyes were classified as having type 1 ROP or aggressive ROP. Data on the zone, primary treatment chosen, injection dose, presence of reactivation and additional treatment were collected and analysed. Results: Seventy infants (131 eyes) with type 1 ROP and 24 infants (45 eyes) with aggressive ROP were included. Anti-VEGF injection was selected as the primary treatment in 74.05% of the infants with type 1 ROP and 88.89% with aggressive ROP. Anti-VEGF injection was selected as the ROP was located in zone I or posterior zone II, and laser ablation was selected when it was located in zone II. The anti-VEGF injection doses varied and tended to be higher in the aggressive ROP group. Infants with aggressive ROP were 2.08 times more likely to require additional treatment than those with type 1 ROP. When ROP reactivation occurred, laser therapy was preferred as an additional treatment. Conclusion: In Korea, the preference for anti-VEGF therapy or laser therapy differed according to ROP subtype, zone and primary or secondary treatment. These findings suggest that ROP treatment are considered according to ROP subtype, location and reactivation.